Kemah Kebangsaan Sebagai Bentuk Komunikasi Moderat Pada Generasi Muda Di Kabupaten Karanganyar - Situ Asih (Universitas PGRI Madiun, 2022)
The diversity that is owned by the Indonesian nation is a wealth that is not owned by other nations. But on the other hand, diversity is one thing that can cause conflict or problems. The diversity of the younger generation group is supported by advances in science and technology if not managed properly it can lead to conflicts that endanger the unity and integrity of the nation. The results of previous studies say that the younger generation who are not wise in using social media can be consumed by issues or information that is not true and hoaxes. The moderate attitude gradually disappeared, changed to an anti-tolerant and radical attitude. Social media as a medium of communication that is widely used by the younger generation often contains things that are anti-tolerant and hoax information. With a descriptive qualitative research approach, researchers try to describe the efforts made by the Karangayar Regency government to foster moderate attitudes and prevent anti-tolerant attitudes among the younger generation. One form of communication carried out by the Karanganyar Regency government through FKUB is to organize a national camp. The activity, which involved interfaith youth, representatives of all sub-districts, was held with the aim of building good communication between interfaith youth in Karanganyar Regency. The national camp organized by the Karanganyar Regency FKUB with full support from the Karanganyar Regency Government, has proven to be effective in fostering a tolerant and moderate attitude among the younger generation.